Предмет:
МатематикаАвтор:
анонимЕсли функция задана формулой f(x) = -x^2 + 3, то
f(5х) = -(5х)^2 + 3 = -25х^2 + 3;
f(x - 2) = - (х - 2)^2 + 3 = -(х^2 - 4х + 2^2) + 3 = -(х^2 - 4х + 4) + 3 = -х^2 + 4х - 4 + 3 = (приведем подобные слагаемые) = -х^2 + 4х - 1;
f(7 - х) = - (7 - х)^2 + 3 = -(7^2 - 14х + х^2) + 3 = -(49 - 14х + х^2 ) + 3 = - 49 + 14х - х^2 + 3 = -46 + 14х - х^2 ;
f(2х + 3) = - (2х + 3)^2 + 3 = -(4х^2 + 12х + 3^2) + 3 = -(4х^2 + 12х + 9) + 3 = -4х^2 - 12х - 9 + 3 = (приведем подобные слагаемые) = -4х^2 - 12х - 6.
Автор:
tomc5crДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть